2016
DOI: 10.1189/jlb.5ru1215-537rr
|View full text |Cite
|
Sign up to set email alerts
|

Leprosy as a model to understand cancer immunosurveillance and T cell anergy

Abstract: Leprosy is a disease caused by Mycobacterium leprae that presents on a spectrum of both clinical manifestations and T cell response. On one end of this spectrum, tuberculoid leprosy is a well-controlled disease, characterized by a cell-mediated immunity and immunosurveillance. On the opposite end of the spectrum, lepromatous leprosy is characterized by M. leprae proliferation and T cell anergy. Similar to progressive tumor cells, M. leprae escapes immunosurveillance in more severe forms of leprosy. The mechani… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
11
1

Year Published

2017
2017
2023
2023

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 8 publications
(12 citation statements)
references
References 89 publications
0
11
1
Order By: Relevance
“…Although ICP have been studied for approximately two decades, many features of their biology and signaling pathways remain unknown. ICP receptors are associated with autoimmunity, suggesting that these molecules play a critical role in immune tolerance and homeostasis ( 7 , 8 ). In chronic infections, T lymphocytes are under persistent exposure to antigens, and this stimulus is commonly associated with T exhaustion ( 20 ).…”
Section: Immune Checkpoints In Leprosymentioning
confidence: 99%
See 4 more Smart Citations
“…Although ICP have been studied for approximately two decades, many features of their biology and signaling pathways remain unknown. ICP receptors are associated with autoimmunity, suggesting that these molecules play a critical role in immune tolerance and homeostasis ( 7 , 8 ). In chronic infections, T lymphocytes are under persistent exposure to antigens, and this stimulus is commonly associated with T exhaustion ( 20 ).…”
Section: Immune Checkpoints In Leprosymentioning
confidence: 99%
“…Recent work has demonstrated that Tregs play a role in M. leprae -specific Th1 unresponsiveness during lepromatous disease ( 33 ). In LL, Th2/Treg polarization seems to be important to disease progression, and multiple factors may be responsible for these events, such as antigen exposure and innate immune activation ( 7 ). Otherwise, TT patients present a cellular immune response polarized to Th1/Th17 ( 31 33 ).…”
Section: T Regulatory Cells (Tregs)mentioning
confidence: 99%
See 3 more Smart Citations